2021
DOI: 10.11604/pamj.2021.38.326.28973
|View full text |Cite
|
Sign up to set email alerts
|

Neurological manifestations in patients with symptomatic COVID-19 admitted to the Bafoussam Regional Hospital, Cameroon

Abstract: Introduction although the main manifestations of COVID-19 are respiratory, several neurological symptoms and complications have also been reported. The pandemic seems to have some epidemiological specificities in sub-Saharan Africa, and this may be reflected in the type and frequency of neurological symptoms. This study aimed to report neurological manifestations associated with symptomatic COVID-19 in a sub-Saharan African setting. Methods we conducted a retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…21 A study by Fogang et al in Cameroon with a broader range of patient ages but a similar mean (54.6 years) reported a delirium rate of 5.6% and an impaired consciousness rate of 10.7%. 22 While conducting this study we observed that many patients were described identically to the patients diagnosed with delirium (confused, agitated, inattentive, etc. ), however the diagnosis of delirium was not documented.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…21 A study by Fogang et al in Cameroon with a broader range of patient ages but a similar mean (54.6 years) reported a delirium rate of 5.6% and an impaired consciousness rate of 10.7%. 22 While conducting this study we observed that many patients were described identically to the patients diagnosed with delirium (confused, agitated, inattentive, etc. ), however the diagnosis of delirium was not documented.…”
Section: Discussionmentioning
confidence: 92%
“…Our results are consistent with previous literature that indicates delirium is associated with worse health outcomes in COVID-19 patients. 16,22,24 In terms of psychiatric history, patients diagnosed with delirium had pre-existing cognitive deficits and history of substance use. Cognitive deficits have been found in older patients to be associated with development of delirium, and we see here a confirmation of studies suggesting that association is also true in younger patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 In a Cameroonian study with 177 COVID-19 patients, 27% had hypertension, 4.5% heart failure, and 1% prior stroke, but none of these were associated with COVID-19 neurological symptoms. 15 In a cross-sectional study in Burkina Faso with 442 patients, 22% had hypertension and 17% CVD, but neither was associated with severe hypoxemia. 16 In a cross-sectional study of 274 patients with long-COVID in Nigeria, 16% had hypertension, but this was not statistically significantly associated with persistent COVID-19 symptoms (aOR, 1.9 [95% CI, 0.3–10.8]), 17 similar to findings from a case-control study in Sudan with 100 COVID-19 cases with hypertension or CVD and 100 controls.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies found no association between preexisting hypertension, CVD, and COVID-19 infection or severity, but compared with the studies above, all 6 were limited by methodologic issues with hypertension/CVD ascertainment, small sample size, and recruitment from a single site. 13–18 The median age ranged from 18 to 55 years, and the samples were 32% to 51% female. Of 4258 patients with COVID-19 found through a cross-sectional community survey in Zambia, neither hypertension (found in 3.8% of patients with COVID-19) nor CVD (found in 0.4%) were associated with COVID-19 infections, but the diagnoses of hypertension and CVD was apparently determined by patient report, which is notoriously unreliable in Africa where many such cases are undiagnosed.…”
Section: Resultsmentioning
confidence: 99%